Cognitive Informatics in Health and Biomedicine Understanding and Modeling Health Behaviors - Patel, Vimla L.; Arocha, Jose F.; Ancker, Jessica S.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
As health care is moving toward a team effort with patients as partners, this book provides guidance on the optimized use of health information and supporting technologies, and how people think and make decisions that affect their health and wellbeing. It focuses on investigations of how general public understand health information, assess risky behaviors, make healthcare decisions, and how they use health information technologies. e-health technologies have opened up new horizons for promoting increased self-reliance in patients. Although information technologies are now in widespread use, there is often a disparity between the scientific and technological knowledge underlying health care practices and the cultural beliefs, mental models, and cognitive representations of illness and disease. Misconceptions based on inaccurate perceptions and mental models, and flawed prior beliefs could lead to miscommunication as well as to erroneous decisions about individuals$1 (Bown health or the health of their family members. Cognitive Informatics in Health and Biomedicine: Understanding and Modeling Health Behaviors presents state of the art research in cognitive informatics for assessing the impact of patient behavior. It is designed to assist all involved at the intersection of the health care institution and the patient and covers contributions from recognized researchers and leaders in the field.s
Section I: Introduction to the Role of Cognitive Issues in Health Behaviors and the Design of Interventions -- 1. Cognition and Behavior Change in Health Care Domain -- 2. Design and Implementation of Behavioral Informatics Interventions -- Section II: Understanding Public Health Beliefs -- 3. Making Sense of Health Problems: Folk Cognition and Healthcare Decisions -- 4. Toward a Framework for Understanding Embodied Health Literacy -- 5. Models of Health Beliefs in South India: Impact on Managing Childhood Nutritional Illnesses -- Section III: Cognition and Health Behaviors -- 6. Health Information Literacy as a Tool for Addressing Adolescent Behaviors, Knowledge, Skills, and Academic Trajectories -- 7. Using Behavior Measurement to Estimate Cognitive Function based on Computational Models -- 8. The Slippery Slope of Sexual Decision-Making in Young Adults: The Role of Social and Cognitive Factors -- 9. Numeracy and Older Immigrants$1 (BHealth: Exploring the Role of Language -- 10. Culturally Appropriate Behavioral Change in Maternal Health: Role of Mobile and Online Technologies Over Time -- Section IV: Information Technology and Cognitive Support -- 11. Addressing health literacy and numeracy through systems approaches -- 12. Aging, Cognition and Technology Systems -- 13. eHealth Literacy as a Mediator of Health Behaviors. Section V: Behavioral Measures and Interventions -- 14. From Personal Informatics to Personal Analytics: Investigating How Clinicians and Experts Reason about Personal Data Generated with Self-Monitoring in Diabetes -- 15. Leveraging Social Media for Health Promotion and Behavior Change: Methods of Analysis and Opportunities for Intervention -- 16. Game Based Behavior Change Methods in Healthcare: The Case of Obesity -- Section VI: Future Directions -- 17. Cognitive Informatics and Health Behaviors: The Road Ahead.s
Keywords: Medicine; Health informatics; Cognitive grammar; Medicine & Public Health; Health informatics; Cognitive Linguistics